Characteristics and direct causes of death in severely ill patients admitted to a neurology department - Lee, Da Heui; Jeong, Seok Young; Shin, Byoung-Soo; Kang, Hyun Goo (Frontiers in Neurology, 2024)
IntroductionThe study aimed to analyze the characteristics of patients admitted to the neurology department of a tertiary hospital who subsequently died, focusing on those with high disease severity.Materials and methodsWe conducted a retrospective cohort study of patients who died among those admitted to the neurology department of a regional tertiary hospital from 2013 to 2021. Clinical, radiological, and laboratory results of the included patients were collected, and their primary diagnoses, duration from time of admission to death, and direct causes of death were analyzed. Furthermore, the patients were categorized into subgroups based on sex (male and female), primary diagnosis (ischemic and non-ischemic stroke), and cancer diagnosis for comparative analysis.ResultsOf 187 deaths, the primary diagnoses were ischemic stroke (131 cases), seizures (19 cases), encephalitis and encephalopathy (18 cases), and other conditions (19 cases). The direct causes of death included ischemic stroke in 68 patients, sepsis in 33, cerebral hemorrhage in 19, pneumonia in 15, acute kidney injury in nine, status epilepticus in seven, and other causes in 36. Pneumonia, cerebral hemorrhage, acute kidney injury, and status epilepticus were the more prevalent direct causes of death in men, whereas ischemic stroke and sepsis were more prevalent in women. Additionally, sepsis, pneumonia, acute kidney injury, and status epilepticus, as direct causes of death, were significantly higher among patients with a primary diagnosis of non-ischemic stroke than among those with a primary diagnosis of ischemic stroke. Furthermore, there were differences in some pre-existing diseases and laboratory findings when comparing between the cancer group and the non-cancer group.DiscussionIschemic stroke was the primary diagnosis and direct cause of death in a high proportion of patients. Other noteworthy direct causes of death were cerebral hemorrhage and infections such as sepsis and pneumonia. Based on these findings, the characteristics and prognoses of patients admitted to neurology departments can be predicted and used for management.